Interleukin-2 receptor alpha as a biomarker for nonalcoholic fatty liver disease diagnosis. Issue 3 (3rd March 2021) - Kao, Wei-Yu; Lin, Yuan-Feng; Chang, I-Wei; Chen, Chi-Long; Tang, Jui-Hsiang; Chang, Chun-Chao; Chang, Yu-Jia; Wang, Weu
Abstract : Background: Two recent studies in the adult and pediatric Nonalcoholic Steatohepatitis-Clinical Research Network (NASH-CRN) cohorts have shown that soluble interleukin-2 receptor alpha (IL2RA) levels increased with fibrosis severity. However, no hepatic study has been conducted in Asian morbidly obese patients who underwent bariatric surgery. In this study, we proposed IL2RA as a biomarker for nonalcoholic fatty liver disease (NAFLD) diagnosis and performed immunohistochemistry (IHC) staining of IL2RA. Methods: This prospective cohort study enrolled 123 morbidly obese patients who underwent bariatric surgery at Taipei Medical University Hospital from October 2016 to June 2018. During bariatric surgery, all patients underwent a wedge liver biopsy under laparoscopic guidance. The diagnoses of NASH and liver fibrosis were made histologically. In IHC of IL2RA, the number of lymphocytes with IL2RA immunoreactivity was counted in five high-power fields (×400, total: 1.19 mm 2 ). Results: Among the 123 patients, the mean age was 35.5 years, mean body mass index (BMI) was 40.6 kg/m 2, 87 (70.7%) were female, 25 (20.7%) had diabetes mellitus, and 57 (46.3%; 11 with non-NAFLD and 46 with steatosis) and 66 (53.7%) were included in the non-NASH and NASH groups, respectively. The NASH group had higher IHC of IL2RA than the non-NASH group. In multivariate analysis, IHC of IL2RA (odds ratio, 1.025; 95% confidence interval, 1.006–1.045; p  =   0.011) and alanine aminotransferase (ALT; odds ratio, 1.045; 95% confidence interval, 1.018–1.073; p  =   0.001) were the independent factors associated with NASH. The area under the receiver operating curve of IL2RA IHC for NASH was 0.627 at the cutoff value of 82 ( p =  0.0113). Conclusion: IL2RA is significantly associated with NASH in morbidly obese patients and would be a useful biomarker for NASH diagnosis.